(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In this article, the issues of the use of information and communication technologies in the process of education and upbringing in higher education institutions will be considered and considered. In recent years, information and communication technologies have dramatically transformed various sectors, with education being one of the most affected. Higher education institutions, in particular, have embraced ICT tools to revolutionize the educational process. The integration of ICT in higher education has reshaped traditional teaching and learning methodologies, making them more interactive, accessible, and student-centered.